2017
DOI: 10.1016/j.infbeh.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin trajectories and social engagement in extremely premature infants during NICU hospitalization

Abstract: Extremely premature infants, born 28 weeks gestation or less, are at high risk for impaired socioemotional development, due in part to exposure to early stressful social experiences that alter brain development. Understanding mediators that link experience with outcomes is necessary to assess premature infant responses to social experiences that are critical to brain development. The hormone oxytocin (OT), released during supportive interactions, has potential as a biomarker of the premature infant’s responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Children with higher CSF OT levels appear to more actively seek parental social interaction for soothing and have a greater interest in social interaction as measured at 6 months of age (54). The only exception to these working hypotheses resides in one study developed in hospitalized premature infants which reported a negative correlation between infant OT levels and social engagement (55). While discordant with all other findings of this section, one should not forget that this study targeted a special infant population characterized as clinically concerning and submitted to high physiological demands to maintain organic homeostasis.…”
Section: Infantsmentioning
confidence: 99%
“…Children with higher CSF OT levels appear to more actively seek parental social interaction for soothing and have a greater interest in social interaction as measured at 6 months of age (54). The only exception to these working hypotheses resides in one study developed in hospitalized premature infants which reported a negative correlation between infant OT levels and social engagement (55). While discordant with all other findings of this section, one should not forget that this study targeted a special infant population characterized as clinically concerning and submitted to high physiological demands to maintain organic homeostasis.…”
Section: Infantsmentioning
confidence: 99%
“…Despite an abundant literature on the role of socio-emotional environment and parental interactions in the neurodevelopmental outcomes of infants born preterm [ 27 ], only a few studies addressed the developmental trajectories of OT in the neonatal period and its balance with cortisol in dyadic interactive contexts [ 11 , 15 ]. In addition to the effect of skin-to-skin contact on OT salivary levels in neonates [ 12 ], and the effects of the maternal speech and singing during painful procedures [ 8 ], no other study addressed the ability of an early intervention to change OT levels in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Its synthesis was notably studied to identify the biological effect of skin-to-skin carrying, where it increases in both parents and children [ 12 ]. Other studies assessed its relationship with parental attachment and showed conflicting results [ 13 , 14 , 15 ]. In addition to its effect on maternal behavior, other roles of OT were demonstrated, including its anti-inflammatory properties both in the developing and mature brain [ 16 ] and a modulatory effect on the hypothalamo-pituitary and adrenal axis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AVP has been implicated in male vulnerability to autism and higher mortality rates in premature male infants [ 131 ]. Altered blood levels of OXT have been reported in children with ASD [ 132 ] and premature infants [ 133 ], underscoring the importance of OXT-AVP pathways in both prematurity and autism.…”
Section: Discussionmentioning
confidence: 99%